Innovative biomimetic parametric timber structures - Kasulu, Kachana; Volichenko, Olga; Abramyan, Philipp; Kariev, Beisen (project baikal, 2025)
This article examines the integration of biomimetic principles and parametric methods with engineered timber in architectural design. Analysing Metropol Parasol, Pompidou-Metz, Pulp Pavilion, ITECH, and Bowooss pavilions shows how biological analogues inspire innovative timber forms. Parametric tools mediate biomimetic logic into efficient, responsive designs. Digital fabrication enhances the versatility, sustainability, and complexity of timber. The study establishes a validated taxonomy that links theory and practice, promoting biomimetic-parametric synergy and interdisciplinary, bio-informed design approaches..